HTERT MNS16A polymorphism in breast cancer: a case-control study. - Zagouri, F.; Sergentanis, T.N.; Gazouli, M.; Tsigginou, A.; Dimitrakakis, C.; Eleutherakis-Papaiakovou, E.; Papaspyrou, I.; Chrysikos, D.; Theodoropoulos, G.; Zografos, G.C.; Antsaklis, A.; Dimopoulos, A.M.; et al. (Molecular biology reports, 2012)
This case-control study aims to investigate the role of HTERT MNS16A polymorphism as a potential risk factors and/or a prognostic marker for breast cancer. 113 consecutive incident cases of histologically confirmed ductal breast cancer and 124 healthy controls were recruited. HTERT MNS16A polymorphism was genotyped (L: long allele, S: short allele); multivariate logistic regression was performed. No significant association was noted either at the overall analysis (OR = 1.57, 95 % CI 0.84-2.93 for heterozygous LS carriers; OR = 1.02, 95 % CI 0.54-1.95 for homozygous SS carriers) or at the subanalyses in premenopausal and postmenopausal women. With respect to survival analysis, HTERT MNS16A polymorphism was not associated with either disease-free survival or overall survival. HTERT MNS16A polymorphism does not seem to be a risk factor for breast cancer in the Caucasian Greek population. Further, larger studies from other countries and subjects seem to be needed as this novel polymorphism is being examined in depth.